2010
DOI: 10.1089/aid.2009.0274
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Modifying or Discontinuing First HAART Regimen and Its Determinants in a Cohort of HIV-Infected Patients from Rio de Janeiro, Brazil

Abstract: Studies on the long-term safety and tolerability of HAART are scarce in developing countries. HAART has been universally available in Brazil since 1997, providing a unique opportunity to evaluate the incidence and risk factors for HAART discontinuation or modification. We analyzed retrospective data from 670 treatment-naive patients followed at the HIV cohort of Evandro Chagas Clinical Research Institute, Oswaldo Cruz Foundation, in Rio de Janeiro, Brazil, who first received HAART between January 1996 and Dece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
45
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 42 publications
5
45
1
2
Order By: Relevance
“…Major adverse effect resulted in the regimen modification was lipodystrophy, followed by hepatotoxicity and rash in the study. Other studies in resource-limited settings showed the consistent results [6]-[8]. …”
Section: Introductionsupporting
confidence: 74%
See 2 more Smart Citations
“…Major adverse effect resulted in the regimen modification was lipodystrophy, followed by hepatotoxicity and rash in the study. Other studies in resource-limited settings showed the consistent results [6]-[8]. …”
Section: Introductionsupporting
confidence: 74%
“…In this study, time to regimen modification due to lipodystrophy was around three times longer than other studies [5],[6]. It might reflect the time lag between the diagnosis of lipodystrophy and regimen modification.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Given the importance of ART adherence to treatment efficacy [1], development of ART resistance [14], and mortality reduction [15], future research is needed to characterize the reasons for treatment interruptions [16]. …”
Section: Discussionmentioning
confidence: 99%
“…An observational, longitudinal, clinical database is maintained on patients receiving primary and specialized outpatient and inpatient HIV care at the clinic; it includes socio-demographic, behavioral, clinical and therapeutic information. Details of the HIV/AIDS clinical cohort can be found elsewhere [7,8]. The IPEC Institutional Review Board reviewed and approved this study.…”
Section: Methodsmentioning
confidence: 99%